Three-dimensional quasi-static interfacial crack growth simulations in thermo-mechanical environment by coupled FE-EFG approach. (December 2016) - Pathak, Himanshu; Singh, Akhilendra; Singh, Indra Vir
Highlights: Coupled FE-EFG approach is used to solve 3-D interfacial crack growth problems under mechanical and thermos-elastic loading. Four enrichment functions are used to capture an interface crack front behaviour. Fatigue life of an interfacial edge crack body is found small as compared to the interfacial centre crack body. Crack gradually moves towards the weak material in case of interfacial crack growth simulations. Thermal shock loading exhibits more fatigue life as compared to equivalent mechanical load. Abstract: This paper presents the three-dimensional interfacial crack growth simulations using coupled finite element and element free Galerkin (FE-EFG) approach under mechanical and thermo-elastic loading. Extrinsic partition of unity (PU) enrichment technique has been employed to model a crack in the domain. Crack face and crack front have been modelled by Heaviside and asymptotic branch enrichment functions respectively whereas a material interface has been modelled by a signed distance function. Modified domain based interaction integral approach has been employed to evaluate the individual stress intensity factors. Standard Paris law of fatigue crack growth has been employed for the life prediction of interfacial cracked geometries. Several interfacial fatigue crack growth problems have been solved by the coupled EF-EFG approach.